2015
DOI: 10.1080/15567036.2011.584271
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Performance and Emission Assessment of a Hydrogen/Diesel Fueled Engine

Abstract: This study investigates the engine performance and exhaust emission of the dual-fuel operation on a single cylinder compression ignition engine from the energetic, exergetic, and sustainability points of view using experimental values. Hydrogen with different concentrations is used as fuel with diesel as the main fuel. Comparative results of the dual-fuel operation with conventional diesel fuel through experimental results demonstrated its benefits for the engine performance. The engine specific fuel consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…The above reading indicates that premixing camphor supports better combustions. Morsy et al [ 65 ] and Gozmen Şanli et al [ 98 ] found that the SI is directly proportional to energy efficiency, similar to our results. The SI defines the economic aspect of fuel's energy conversion technology.…”
Section: Resultssupporting
confidence: 92%
“…The above reading indicates that premixing camphor supports better combustions. Morsy et al [ 65 ] and Gozmen Şanli et al [ 98 ] found that the SI is directly proportional to energy efficiency, similar to our results. The SI defines the economic aspect of fuel's energy conversion technology.…”
Section: Resultssupporting
confidence: 92%
“…This was caused by hydrogen gas replaced the inducted air within the cylinder, thus it led to the overall mixture became slightly richer as explained earlier and the concentration of oxygen was also lower, thereby, lower in-cylinder temperature suppress the NO formation. Similar results were also noticed by Morsy et al [20] at low load operation. It has been reported in the literature Pan et al [21] that if unburned hydrogen present in the in-cylinder behave as a diluents which reduce NO x formation, moreover hydrogen's specific heat capacity is slightly higher than N 2 .…”
Section: Emission Characteristicssupporting
confidence: 90%